UTILIZING WHATSAPP APPLICATION FOR TEACHING INTEGRATED ENGLISH (A CASE STUDY AT UNIVERSITY OF TECHNOLOGY YOGYAKARTA) - Dewi, Septi Riana (Universitas Muria Kudus, 2019)
This study aimed to illustrate some learning activities in Integrated English class byutilizing WhatsApp application and how the students respond to its implementation. The study was conducted in Accounting Department at University of Technology Yogyakarta. The subject of this study was 66 students in Accounting Class A of 2018/2019 Academic Year. The instruments to gather the data were observation, questionnaires and unstructrured interview. The result of this study showed that WhatsApp Application could be utilized as one of the beneficial devices to assist students in learning integrated English and there were positive responses from students during the implementation of WhatsApp in their learning process.